INTERPRETATION OF TRADEMARK WITH DECEPTIVE SIMILARITY IN INDIA - Chinmaya Kumar Mohapatra, Amrita Mishra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the area of present era of globalisation and the fast trading speed, it is extremely important for any business to develop its identity on the minds of the consumers of shoppers. Trademark thus plays a crucial role in creating this brand and contributes to revenue generation. However, when a company name furthers the chance of successful venture, and it becomes incredibly subject to exploitation or infringement. It must be remembered. However one infringement approach is through the development of a "disappointingly similar" trademark to the current one, in order to confuse consumers and leverage the already developed goodwill of the trademark. This not only jeopardizes the reputation, but rather the monetary disruption of its pattern with respect of the name. This paper examines the concept of the disappointing similarity of design patents in India and highlights the court's position in understanding the meaning of disappointing similitude even beyond basic context of the phrase in law for justice..